Revisiting the association between temperature and COVID-19 transmissibility across 117 countries - Chen, Simiao; Prettner, Klaus; Cao, Bin; Geldsetzer, Pascal; Kuhn, Michael; Bloom, David E.; Bärnighausen, Till; Wang, Chen (ERJ Open Research, 2020)
The association between ambient temperature and coronavirus disease 2019 (COVID-19) transmissibility has important implications for containing the disease's spread, yet it is still highly debated. Using a dataset including 65 Chinese cities, Yao et al. [1] found no significant association between COVID-19 transmissibility and temperature or ultraviolet (UV) radiation. Using a dataset including 154 Chinese cities, Ran et al. [2] reran the analyses and found a nonlinear negative association between temperature and COVID-19 transmissibility.